Koch snowflakes batik design / Norzieha Mustapha ...[et al.] - Mustapha, Norzieha; Md Yasin, Roliza; Awang, Junaidi; Abd Rhani, Norarida; Mat Nashir @ MohdNasir, Roziani; Wan Yusof, Wan Roslini (2020)
Batik in Malaysia is a very popular textile, especially in Malaysia's east coast, Kelantan, Terengganu and Pahang. Its uniqueness in batik designs reflecting local identity, distinguish it from its counterpart, the Indonesian batik. The most popular motifs in Malaysian batik are leaves and flowers as well as some geometric designs such as spiral. However, more innovative ideas are needed to meet the demand in designing Malaysian batik. An effort to provide such great inspiration to the designer is through a project using mathematics geometry with the aid of sophisticated computer software and graphics. Mathematics and art have a long historical relationship, commonly known as fractals. Koch snowflake is a kind of geometrical shape and is one of the earliest fractals. Koch snowflake has great potential to be a motif design for Malaysian batik because of its simplicity and beauty and yet never been extensively explored before. The impact of this product to the society is to demonstrate the importance of mathematics in the world of fashion as well as enhancing the commercialization of Malaysian Batik using fractals